Lutein Leads to a Decrease of Factor D Secretion by Cultured Mature Human Adipocytes - Yuan Tian; Aize Kijlstra; Johan Renes; Martin Wabitsch; Carroll A. B. Webers; Tos T. J. M. Berendschot (Journal of Ophthalmology)
Purpose. Complement plays an important role in the pathogenesis of age related macular degeneration (AMD) and trials are currently being conducted to investigate the effect of complement inhibition on AMD progression. We previously found that the plasma level of factor D (FD), which is the rate limiting enzyme of the complement alternative pathway, was significantly decreased following lutein supplementation. FD is synthesized by adipose tissue, which is also the main storage site of lutein. In view of these findings we tested the hypothesis whether lutein could affect FD synthesis by adipocytes. Methods. A cell line of mature human adipocytes was incubated with 50 μg/mL lutein for 24 and 48 h, whereafter FD mRNA and protein expression were measured. Results. Lutein significantly inhibited adipocyte FD mRNA expression and FD protein release into adipocyte culture supernatants. Conclusions. Our earlier observations showing that a daily lutein supplement in individuals with early signs of AMD lowered the level of circulating FD might be caused by blocking adipocyte FD production.